Exchange Rate Adjustment and Relative Size of the Depreciating Bloc: A Comment - Weisbrod, Burton A. (The Review of Economics and Statistics, 1956)
In his article, Exchange Rate Adjustment and Relative Size of the Depreciating Bloc, Professor Orcutt set out to attack the notion that by a large bloc versus the rest of the world generally would be substantially less effective than depreciation by a small country versus the rest of the world. Indeed, he goes so far as to conclude that for the case of actual large blocs, such as the dollar bloc or the sterling bloc, application of the model developed in this paper would seem to indicate that effectiveness of depreciation would be substantially greater than in the case of the small country versus the rest of the world. This conclusion merits evaluation.